2022-RA-1048-ESGO Circulating HPV cell-free DNA in cervical cancer. (20th October 2022) - Mittelstadt, Suzana; Schroeder, Christopher; Kelemen, Olga; Engler, Tobias; Admard, Jakob; Gschwind, Axel; Koch, Andre; Wörz, Sarah Elisabeth; Oberlechner, Ernst; Hoffmann, Sascha; Andress, Jürgen; Neis, Felix; et al.
Abstract : Introduction/Background: Human papillomavirus (HPV) related cervical cancer is the fourth most frequent cancer in women worldwide. Currently patient follow-up and therapy monitoring is solely based on clinical examination and cross-sectional imaging. Liquid biopsies for cell-free circulating tumor DNA in cancer are a novel biomarker to detect treatment response, residual disease, and relapse. The aim of this study was to investigate the potential use of cell-free circulating HPV-DNA (cfHPV-DNA) in plasma samples of patients with cervical cancer. Methodology: In this proof-of-concept study cfHPV-DNA levels were measured using a highly sensitive Next-Generation-Sequencing-based approach targeting a panel of 13 high-risk HPV-types. For nine patients cfHPV-DNA sequencing was compared to HPV testing in corresponding paraffin embedded tumor sample. Sequential plasma samples were taken from four patients receiving primary chemoradiation. Results: A total of 70 blood samples was collected from n=35 patients. cfHPV-DNA was successfully detected in 25/35 (71%) patients; of them, 8 patients had some surgical pretreatment when the sample was collected. A significant correlation between tumor burden and cfHPV-DNA detection was observed: while cfHPV-DNA was detectable in most patients (20/22) with locally advanced or metastatic disease (FIGO IB3 – IVB), detection was successful in only 5/13 patients with early-stage disease (FIGO IA – IB2), p<0.005. When pretreated patients were excluded, the detectable rate was 100% (18/18) for advanced stages and 55% (5/9) for early stages. HPV-types detected in plasma samples matched results from tumor tissue HPV testing. Sequential sampling for patients under primary chemoradiation showed a dynamic decrease of cfHPV-DNA levels corresponding treatment response in all patients. Conclusion: In this proof-of-concept study we were able to detect cfHPV-DNA in plasma samples of patients with primary and recurrent cervical cancer. Our findings may hold potential to develop a powerful and easily accessible tool in cervical cancer management.